THE IMPACT OF MOTOR VEHICLE ACTIVITY ON AGRICULTURAL OPERATIONS: EFFICIENCY, SUSTAINABILITY, AND FUTURE PROSPECTS - Samadov Muhiddin Akhadovich (Galaxy International Interdisciplinary Research Journal, 2024)
In agriculture, transportation, efficiency and storage of goods by means of transport play an important role. An additional consideration is the variety of agricultural applications in Ushbay farm vehicles, from field preparation and planting to harvesting and transportation. We analyze the impact of transport production on resource management, soil, energy consumption and needs. In addition, we will discuss the contribution to the agricultural vehicle manufacturing sector and development trends such as more efficient and effective agricultural vehicle production, precision agricultural technologies and alternative production processes.